2019
DOI: 10.1021/acs.jpcc.9b04198
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Langmuir Model: A Simpler Approach to Modeling Capacitive Deionization

Abstract: Capacitive deionization (CDI) is emerging as an environmentfriendly and energy-efficient water desalination option for meeting the growing global demand for drinking water. It is important to develop models that can predict and optimize the performance of CDI systems with respect to key operational parameters in a simple way. Such models could open up modeling studies to a wider audience by making modeling more accessible to researchers. We have developed the dynamic Langmuir model that can describe CDI in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 50 publications
(88 reference statements)
2
58
0
Order By: Relevance
“…Previous work has further demonstrated that the linear relationship holds both for anions and cations and can be employed even for solutions containing other ionic species than the investigated pair. 39 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has further demonstrated that the linear relationship holds both for anions and cations and can be employed even for solutions containing other ionic species than the investigated pair. 39 …”
Section: Resultsmentioning
confidence: 99%
“…If there are multiple ions in the solution, the ions of similar charges block the same sites (exchange c ads z for ∑ i z ( i ) c ads ( i ) ). Apart from that, every ion can be considered separately 39 ( eq 6 ). While this expression is complicated to implement, a simpler result can be derived for the relative adsorption between a pair of ionic species in a multi-ion solution at equilibrium.…”
Section: Theorymentioning
confidence: 99%
“…Thus, ionic species can have both a positive and negative effect on microbial neutralization. Figure 4A shows that the initial fast conductivity transition period (period 1) has the highest mass transfer rate of ions toward the electrode surface (Demirer et al, 2013 ), which reduces with time as the electrode approaches saturation (Nordstrand and Dutta, 2019 , 2020 ). The lower quantity of live bacterial cells in period 1 ( Figure 4B ) is plausible as the electric field strength between the CDI device electrodes is the strongest during period 1.…”
Section: Discussionmentioning
confidence: 99%
“…In capacitive deionization (CDI) [8][9][10][11], the electroadsorption process (from saline water) takes place in a cell comprising two electrodes separated by a spacer (Figure 1), and the ion adsorption is utilized to remove ions from the water [7]. Modeling of CDI processes has evolved in different directions [9,[12][13][14][15], wherein models consider the same underlying physics but with widely varying Herein, we discuss the underlying model-independent physics governing electroadsorption. Primarily, this is used as a starting point for comparing the approaches and tools used in three different CDI models: the modified Donnan (mD) model [7][8][9][16][17][18], the Randles circuit [12], and the dynamic Langmuir (DL) model [13,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Modeling of CDI processes has evolved in different directions [9,[12][13][14][15], wherein models consider the same underlying physics but with widely varying Herein, we discuss the underlying model-independent physics governing electroadsorption. Primarily, this is used as a starting point for comparing the approaches and tools used in three different CDI models: the modified Donnan (mD) model [7][8][9][16][17][18], the Randles circuit [12], and the dynamic Langmuir (DL) model [13,19,20]. Crucially, we add value by discussing how tools used in the respective models could be implemented to enhance the other models.…”
Section: Introductionmentioning
confidence: 99%